„Mundus inversus" ossia sui principi carnevaleschi nella pubblicità televisiva italiana - Kornacka, Barbara (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2005)
Carnival rules in Bakhtin's understanding as a system of inversions of the hierarchy of rules concerning the most varied aspects of life and culture is a key to comprehend the texts and pictures of Italian TV advertisement of the 1990s which appears as an element of carnivalization of modern Italian culture. Mésalliance and family relationships between people, values and concepts which are distant from one another in the hierarchy, profanations and lowering present themselves in advertisements as examples of carnival inversions on the vertical axis. However, the topsy-turvy world is a polar inversion on the inside-outside axis. Masks and travesties covering the reality mean directing to the inside what is usually outside. Eccentric behavior and attitudes determine a reverse direction of polar carnival inversions, however ambivalent pictures make distant semantic fields close. Carnivalization of Italian TV advertisement confirms a thesis about carnivalization of postmodern culture.
„Mundus inversus" or on carnival principles in the Italian commercial television